Identification and typology of political signs in Indonesia: A semiotic approach to political communication - Aulia, Faradilla Hasby; Myrna Sakinah (Lililacs Journal, 2025)
This study identifies and classifies political signs as iconic, indexical, and symbolic, examining their role in Indonesian political campaigns and public discourse. Iconic signs, such as logos and national emblems, convey ideological values and collective identities. Indexical signs reflect the socio-political climate and the electorate’s public sentiments. Symbolic signs, including slogans and legislative acts, encapsulate broader societal meanings and political agendas. Through qualitative analysis, this study explores the mechanisms by which signs engage citizens and influence political narratives. In the end, this study aims to deepen the understanding of political communication in Indonesia by deconstructing the intricate relationships between political signs and the country’s dynamic democratic situation. The findings highlight the significance of semiotic analysis in revealing the complex relationships between political power, meaning, and sign, offering insights into the changing nature of political engagement in Indonesia.